PERLINDUNGAN KONSUMEN TERHADAP KETIADAAN LABEL HALAL PADA PRODUK FARMASI MENURUT UNDANG-UNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL - Hendrian Wulansari; Anna Maria Tri Anggraini (Fakultas Hukum Universitas Tarumanagara, 2018)
This study discusses consumer protection against the absence of halal label on pharmaceutical products according to Law No. 33 of 2014 on Halal Product Guarantee. Based on the existing findings that the presence of medicinal products are still many who use materials that are not kosher. Therefore, an effort is needed to provide consumer rights protection to the certification and labeling of halal products. The problem why in the pharmaceutical products are not included halal label? How about consumer protection against pharmaceutical products that do not include halal label? Ingi research method using normative legal research methods. The result data showed that the absence of halal label on pharmaceutical products due to the factors that influence it is because of the difficulty of finding replacement materials for medicines because 90 percent of the drugs are imported from other countries where there is no guarantee of halal. In the near future the producers of drugs are also experiencing constraints because they have to conduct research on raw materials because of the difficulty of the origin of the material also has its own complexity so it takes a long time. On the other hand, the equipment used for the production process, production site, processing, storage, packaging and sales and presentation should be made separately between halal and non-halal certified products / products. Consumer protection against pharmaceutical products that do not include halal labels should have 3 (three) supervisory systems that are preventive by looking at enrollment activities, with special supervision of food cases, medicines and kosher cosmetics that can result in widespread impact and incidental surveillance systems namely the process of supervision by law enforcers on halal food safety and safety done by means of sudden inspection (sidak). There needs to be a systematic joint effort of the government and relevant stakeholders to encourage the maker of halal drug products and raise awareness of the Muslim community about the importance of halal products. It aims to protect Muslims from consuming unlawful products.